Pembuatan Bokasi Berbahan Dasar Jerami Bagi Masyarakat Kelompok Tani Di Desa Borikamase Kabupaten Maros - Safitri, Dian; Magfirah, Nurul; Irmawaty, Irmawanty; Syam, Haerul (Biosel Biology Science and Education, 2021)
The large number of rice fields in Borikamase Village, resulting in high production of hay, requires an appropriate effort to use straw into organic fertilizer or bokashi which is environmentally friendly as well as safe for plants. The use of straw into bokashi or organic fertilizer needs to be taught to the farming community, so the community service team focuses on providing assistance and training to the community in utilizing straw as a raw material in making bokashi by using microorganisms as the source of fermentation. In addition, the high price of synthetic fertilizers on the market makes farmers in Borikamase Village feel heavy in providing nutritional supplies to their agricultural areas, so that this training is expected to help farmers by obtaining fertilizers that are cheap, safe, and of good quality to fertilize. The existence of biotechnology applications, provides the right solution in overcoming the damage to bald mountains and the scarcity and high price of synthetic fertilizers, namely by processing straw into bokashi or organic fertilizers with high nutrient content and are safe for the environment. In addition, providing knowledge and skills for farming communities as agents of reform in restoring ecosystem balance through the application of bokashi made of straw on rice fields. Keywords: Training, Mentoring, Boricamase, Straw